Cebuano fiction = Sugilanong sugboanon : until 1940 - Kintanar-Alburo, Erlinda (Quezon City : Ateneo de Manila University Press, 2009)
An anthology of prose fiction gathered from the mid-1800s until the year 2005. Each volume contains short stories or excerpts from short stories or novels in Cebuano.
Cebuano and English.